2015
DOI: 10.1038/srep13174
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of four digital PCR platforms for accurate quantification of DNA copy number of a certified plasmid DNA reference material

Abstract: Digital polymerase chain reaction (dPCR) is a unique approach to measurement of the absolute copy number of target DNA without using external standards. However, the comparability of different dPCR platforms with respect to measurement of DNA copy number must be addressed before dPCR can be classified fundamentally as an absolute quantification technique. The comparability of four dPCR platforms with respect to accuracy and measurement uncertainty was investigated by using a certified plasmid reference materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
112
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(116 citation statements)
references
References 15 publications
3
112
0
Order By: Relevance
“…They also found a larger partition volume for the Biomark platform than earlier reported by Bhat et al [62]. Furthermore, the data collected by Dong et al [55] and Pinheiro et al [45] indicate that the partition volume differs between samples and/or cartridges, further providing evidence of the need for partition volume verification. The partition volume used by the QX100 and QX200 ddPCR systems (Bio-Rad) has since been updated to 0.85 nL.…”
Section: Partition Volumementioning
confidence: 63%
See 2 more Smart Citations
“…They also found a larger partition volume for the Biomark platform than earlier reported by Bhat et al [62]. Furthermore, the data collected by Dong et al [55] and Pinheiro et al [45] indicate that the partition volume differs between samples and/or cartridges, further providing evidence of the need for partition volume verification. The partition volume used by the QX100 and QX200 ddPCR systems (Bio-Rad) has since been updated to 0.85 nL.…”
Section: Partition Volumementioning
confidence: 63%
“…Furthermore, Pinheiro et al [45] discussed the importance of an accurate volume estimation in more detail, and Corbisier et al [57] found that concentrations of reference materials were underestimated due to real droplet volumes 8 % lower than the provided 0.91 nL. This finding was confirmed by Dong et al [55] who found that the droplet volume provided for the Raindrop ddPCR platform was also overestimated (4.39 pL instead of 5 pL, or a 14 % overestimation). They also found a larger partition volume for the Biomark platform than earlier reported by Bhat et al [62].…”
Section: Partition Volumementioning
confidence: 79%
See 1 more Smart Citation
“…The principle of ddPCR involves subdividing a single PCR reaction mixture into many small partitions and each undergoing the PCR reaction separately (32). Several studies have reported using ddPCR to determine the relative copy numbers of plasmids (33,34). According to our results, the relative copy numbers of pBM1, pBM2, pBM3, and pBM4 were calculated as 82, 24, 34, and 16 copies per chromosome equivalent using the ddPCR method.…”
Section: Structure Of the Predicted Origin Of Replication In Plasmimentioning
confidence: 99%
“…There are multiple sequencing platforms that are available for analysis of ctDNA and these platforms all have some various advantages and disadvantages (12). Platforms such has real-time quantitative PCR (qPCR), the Scorpion Amplification-Refractory Mutation System (ARMS) and droplet digital PCR (dPCR) can provide high sensitivity for detection of known genomic alterations and relatively easy to integrate into the clinical workflow with easy bioinformatic burden.…”
Section: Detection and Analysismentioning
confidence: 99%